Early birds, night owls, and tireless/recurring itinerants: An exploratory analysis of extreme transit behaviors in Beijing, China. (October 2016) - Long, Ying; Liu, Xingjian; Zhou, Jiangping; Chai, Yanwei
Abstract: This paper seeks to understand extreme public transit riders in Beijing using both traditional household surveys and emerging new data sources such as Smart Card Data (SCD). We focus on four types of extreme transit behaviors: public transit riders who (1) travel significantly earlier than average riders ('early birds'); (2) ride in unusual late hours ('night owls'); (3) commute in excessively long distance ('tireless itinerants'); and (4) make significantly more trips per day ('recurring itinerants'). SCD are used to identify the spatiotemporal patterns of these four extreme transit behaviors. In addition, household surveys are employed to supplement the socioeconomic background and tentatively profile extreme travelers. While the research findings are useful to guide urban governance and planning in Beijing, our methodology and procedures can be extended to understand travel patterns elsewhere.